Improving Elementary School Students' Essays Writing Skills by Using The Brainwriting Learning Model Assisted by Storybird - Tiana Dara Lugina; Prana Dwija iswara; Asep Saefudin; Arie Rakhmat Riyadi (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThis study aims to determine the effect of the Brainwriting learning model assisted by storybird on narrative essay writing skills of phase C elementary school students in grade 5. This study used a quasi-experiment method of one group pretest-posttest design with purposive sampling. This research was conducted at Public Elementary School (SDN) 015 Kresna, Bandung City, West Java Province with a sample of 30 people. Data collection was carried out using test and non-test instruments. The test carried out is writing a narrative essay with a narrative essay assessment rubric consisting of 5 indicators, namely content, organizational structure, linguistic aspects, linguistic characteristics and types of narrative essays. The collected data were analyzed using IBM SPPS 29 to analyze the hypothesis with parametric statistics, namely paired sample t-test and non-parametric Wilcoxon test. First, normality and homogeneity tests were conducted with Shapiro-Wilk analysis. The results of data analysis show that significant (2-tailed) <0.05 so that H0 is rejected and H1 is accepted. It can be concluded that there is a significant difference between before and after the treatment of the Brainwriting learning model assisted by storybird.Keywords: brainwriting, narrative essay, storybird, writing skills. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Brainwriting berbantuan storybird terhadap keterampilan menulis karangan narasi siswa sekolah dasar tahap C kelas 5. Penelitian ini menggunakan metode kuasi eksperimen dengan desain one group pretest-posttest dengan purposive sampling. Penelitian ini dilakukan di Sekolah Dasar Negeri (SDN) 015 Kresna Kota Bandung Provinsi Jawa Barat dengan sampel sebanyak 30 orang. Pengumpulan data dilakukan dengan menggunakan instrumen tes dan non tes. Tes yang dilakukan adalah menulis esai naratif dengan rubrik penilaian esai naratif yang terdiri dari 5 indikator yaitu isi, struktur organisasi, aspek kebahasaan, ciri kebahasaan dan jenis esai naratif. Data yang terkumpul dianalisis menggunakan IBM SPPS 29 untuk menganalisis hipotesis dengan statistik parametrik yaitu uji t sampel berpasangan dan uji non parametrik Wilcoxon. Pertama, uji normalitas dan homogenitas dilakukan dengan analisis Shapiro-Wilk. Hasil analisis data menunjukkan signifikansi (2-tailed) < 0,05 sehingga H0 ditolak dan H1 diterima. Sehingga dapat disimpulkan bahwa terdapat perbedaan yang signifikan keterampilan menulis karangan narasi siswa antara sebelum dan sesudah perlakuan menggunakan model pembelajaran Brainwriting berbantuan storybird.Kata kunci: brainwriting, karangan narasi, storybird, keterampilan menulis.